A study on possibility of commuting trip using private motorized modes in cities around the world: Application of multilevel model. (December 2015) - Choi, Hyunsu; Ahn, Yoongho
Highlights: We built a huge DB shows individual trip behaviors 78 large cities in the world. We explain the variances on probability of commute trip by private modes (PCTP). Multilevel model is applied for hierarchical DB on city and individual variables. Existence of variance in PCTP among the cities and individual factors is confirmed. Generally individual effects on PCTP are stronger than those of city level factors. Abstract: The focus of the current research was to evaluate how the individual's social characteristics and urban infrastructure impacts the usage of Private Motorized Modes (PMM). Based on individual and urban characteristics a multilevel analysis was conducted on the possibility of commuting trip by private motorized modes on the rush time of 78 cities around the world. Also the selected cities were classified through a principal component analysis, and based on the classification the impact of and urban variables on the possibility of commuting trips made by private motorized modes (PCTP) was verified. Results showed a diverse range of variables related to the usage of PMM, as well as the urban structure and railway lengths being an important variable in travel behavior.